2009
DOI: 10.1590/s0103-21002009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Auto-proteção profissional e cuidado de enfermagem ao paciente soropositivo ao HIV: duas facetas de uma representação

Abstract: Objective: To identify and describe the approaches for professional self-protection in the social context of the nursing care for HIV patients. Methods: This was a qualitative descriptive study. A sample of 40 professional nurses from a university hospital in Rio de Janeiro participated in the study. Data were collected through interviews and analyzed with ALCESTE 4.7 software. Results: Professional selfprotection is an important element of nursing care for HIV patients. Self-protection included the use of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
1
5
0
9
Order By: Relevance
“…9 Em estudo realizado com 40 profissionais de saúde no Rio de Janeiro, os entrevistados relataram que muitos acidentes de trabalho ocorrem devido ao desuso dos EPI, além da carga horária intensa e/ou descuido ao manusear perfurocortantes. 10 Outro estudo, ao investigar a prevalência das notificações de acidentes envolvendo material biológico que acometeram os profissionais da área da saúde e a equipe de saúde bucal, revelou que de um total de 377 notificações, 94,4% envolveram profissionais de saúde e 5,6% a equipe de saúde bucal. Além disso, 93,6% das notificações eram de profissionais do sexo feminino, o tipo de exposição mais relatada foi á percutânea (95,2%) e o material biológico referido na maioria das notificações foi o sangue (88,6%).…”
Section: Discussionunclassified
“…9 Em estudo realizado com 40 profissionais de saúde no Rio de Janeiro, os entrevistados relataram que muitos acidentes de trabalho ocorrem devido ao desuso dos EPI, além da carga horária intensa e/ou descuido ao manusear perfurocortantes. 10 Outro estudo, ao investigar a prevalência das notificações de acidentes envolvendo material biológico que acometeram os profissionais da área da saúde e a equipe de saúde bucal, revelou que de um total de 377 notificações, 94,4% envolveram profissionais de saúde e 5,6% a equipe de saúde bucal. Além disso, 93,6% das notificações eram de profissionais do sexo feminino, o tipo de exposição mais relatada foi á percutânea (95,2%) e o material biológico referido na maioria das notificações foi o sangue (88,6%).…”
Section: Discussionunclassified
“…The results showed seven categories that explain the definitions and images of HIV/AIDS, ways of transmission and prevention, prejudice and 35 It was observed that the professional selfprotection was an important element of care, covering: the use of personal protective equipment; the handling and disposal of sharp equipment; occupational exposure in health care management; and forms of care. Identify and compare the social representations of nursing care to HIV patients for nursing professionals.…”
Section: -Social Representations About People Living With Hiv/aids Obmentioning
confidence: 99%
“…The representation of children as their future present, generating greater psychological distress for nurses. A study 35 pointed professional self-protection as a care element associated with the risk of exposure to the virus.…”
Section: -Social Representations About People Living With Hiv/aids Obmentioning
confidence: 99%
See 1 more Smart Citation
“…Há As RS do cuidar estão associadas mais ao autocuidado do que ao cuidado com o outro (13) . Os profissionais afirmam que cuidar de portadores do HIV, é como cuidar de qualquer outro cliente, porém há uma maior necessidade de proteção contra a contaminação (14) .…”
Section: Categoria 3 -Vulnerabilidade Profissional E Pessoalunclassified